Microwave energy applications management: Weed management MANMIC: Manual microwave (2.45GHz, 250W) - Carlo Groffils (Global Journal of Ecology - Peertechz Publications, 2022)
Today herbicides are the main method of weed management in agriculture/horticulture, community green servicing and private individuals Table 1.